Analysis of Implementation of SKKNI Sub Funding and Services for Graduate of Vocation in Banking Sector - Aidha Trisanty (At-Taqaddum, 2021)
The Indonesian National Work Competency Standards (SKKNI) are efforts to produce graduates ready for work according to industry needs. This includes the SKKNI for the sub-field of Funding and Services, covering four levels of qualifications for a prospective banker that include Teller, Customer Service, Funding Sales Representative, and Funding Product Development Manager. This study aims to determine the implementation of the SKKNI for Sub Financing and Services for Diploma III graduates at the current SMK level. This research is a qualitative descriptive study using observation and interview methods for data collection. The population in this study were all commercial banks and Islamic banks in Yogyakarta. From the questionnaires distributed to users, fourteen banks consisted of 9 (nine) conventional banks, and 5 (five) Islamic banks filled out the questionnaire. Constraints in the application of the SKKNI are caused by the qualifications of the positions regulated in the SKKNI. The gap between the provisions in the SKKNI and the regulations in force in banking is an obstacle for vocational schools in preparing graduates who meet industry demands.